Challenges to medical professionalism / Mohammed Fauzi Abdul Rani. - Abdul Rani, Mohammed Fauzi (Universiti Teknologi MARA Cawangan Selangor, 2017)
Medical professionalism is the basis of the trust given to doctors by the society. At the heart of it is a doctor who must ensure the well-being of patients at all times and always protect them from harm. In doing so they are expected to be competent, compassionate, open and honest, respect patient's autonomy and always guard their confidentiality. These qualities enable doctors to earn that trust, and accord them their professional status and privileges, and axiomatic of the essence of a good doctor [1]. As a concept, medical professionalism is defined with four basic characteristics [2]. They are an altruistic vocation linked to public service, adherence to defined standards and ethical codes, the ability to apply a body of specialist knowledge and skills, and a high degree of self-regulation over professional membership and work organization. Other qualities that are fundamental to the understanding of medical professionalism include advocacy and justice, leadership, collaboration and collegiality. These values are timeless but they do not operate in a vacuum, the dynamics of a society change over time leading to different demands and expectations from the medical profession [3]. Doctors therefore must be cognizant that these changing circumstances represent new challenges and require them to adjust and refine their professional values to effectively fulfill their obligation to the society. Two key issues that will be touched here are the changing landscape of healthcare in this country as it moves from public to private healthcare and the question of professional self-regulation and organization.